Evidence of Positive Selection for a Glycogen Synthase (GYS1) Mutation in Domestic Horse Populations. (8th November 2013) - McCoy, Annette M.; Schaefer, Robert; Petersen, Jessica L.; Morrell, Peter L.; Slamka, Megan A.; Mickelson, James R.; Valberg, Stephanie J.; McCue, Molly E.
Abstract: A dominantly inherited gain-of-function mutation in the glycogen synthase ( GYS1 ) gene, resulting in excess skeletal muscle glycogen, has been identified in more than 30 horse breeds. This mutation is associated with the disease Equine Polysaccharide Storage Myopathy Type 1, yet persists at high frequency in some breeds. Under historical conditions of daily work and limited feed, excess muscle glycogen may have been advantageous, driving the increase in frequency of this allele. Fine-scale DNA sequencing in 80 horses and genotype assays in 279 horses revealed a paucity of haplotypes carrying the mutant allele when compared with the wild-type allele. Additionally, we found increased linkage disequilibrium, measured by relative extended haplotype homozygosity, in haplotypes carrying the mutation compared with haplotypes carrying the wild-type allele. Coalescent simulations of Belgian horse populations demonstrated that the high frequency and extended haplotype associated with the GYS1 mutation were unlikely to have arisen under neutrality or due to population demography. In contrast, in Quarter Horses, elevated relative extended haplotype homozygosity was associated with multiple haplotypes and may be the result of recent population expansion or a popular sire effect. These data suggest that the GYS1 mutation underwent historical selection in the Belgian, but not in the Quarter Horse.